Costa Rican legislation and its relationship with the modern bioeconomy - Sánchez Gómez, José Ignacio (2021)
The historical development of the concept of bioeconomy has been characterized by being immersed in a process of constant dynamism and theoretical evolution, fostering not only numerous definitions but also various strategies that allow a smoother application. This new model has led governments to reconsider the position that regulatory frameworks should take to align with the development of the three basic cornerstones of the bioeconomy (biotechnology - biomass - biodiversity) and thus contribute to achieving the sustainable development goals. The objective of this research was to analyze the strengths and weaknesses of the Costa Rican legislative system in relation to the development of the bioeconomy, through a literature review in the list of updated Costa Rican laws of the year 2017, issued by the Department of Parliamentary  Services of the Legislative Assembly, finding as results, a total of 58 different legal instruments (laws, policies, decrees) that contribute positively to production and conservation from bioeconomic principles, one limiting legislation in the practice of bioeconomy, and nine legal tools that hinder production but contribute to conservation, resulting in an extensive legal framework that does not require the creation of laws, but only central coordination of all the tools it already has.